AN INVESTIGATION INTO THE INFLUENCE OF CULTURE ON EMPLOYABILIY AND WORK ETHIC, AND THE ROLE OF TERTIARY EDUCATORS ON GRADUATES PREPAREDNESS IN BOTSWANA - Ndung’u, Virginiah (European Scientific Journal, ESJ, 2014)
Botswana, though rated as one of the poorest countries in Africa at independence, has through fiscal discipline and sound management, transformed herself to a middle-income country. However, she remains largely dependent on diamond, hence the need to diversify through among others the creation of skilled workforce. In the GCR2013-2014, 2 out of the top 4 factors identified as the most problematic factors for doing business in thecountry were poor work ethic in national labour force (for the sixth consecutive year) andinadequately educated workforce. Poor work ethic in Botswana can be traced from as far back as during colonial time and has persisted up to date. According to Kartha, D.(2012), culture encompasses among others, attitude, beliefs and values, all of which impacts deeply on one’s attitude toward life and work. One of the goals of education is to prepare young people to participate in paid work as employees or self-employed. However the education programme in Botswana has been criticized as weak in terms of among others “less relevant for the labour market". NDP10 identifies the challenge of training high quality graduates with skills relevant to the country’s economic and social development and ability to compete in global labour markets. Hence there is urgent need to re-look the educators’ role in equipping graduates with the necessary employability skills and work ethic.